(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Supartha IW, Susila IW, Sumiartha IK, Rauf A, Cruz LBDC, Yudha IKW, Utama IWEK, Wiradana PA. 2021. Preference, population development, and molecular characteristics of Spodoptera exigua (Lepidoptera: Noctuidae) on shallot cultivars: A field trial scale. Biodiversitas 23: 783-792. The beet armyworm, Spodoptera exigua Hubner (Lepidoptera: Noctuidae), is a polyphagous insect that is the main pest and is responsible for the decline in shallot production in Indonesia. This study aims to (i) analyze preferences; (ii) colonization time; (iii) population development; (iv) attack of armyworms according to plant phenology in the shallot cultivars; and (v) identification species of armyworms. The research was conducted in Bangli Village, Tabanan Regency, Bali Province, Indonesia. The research design used was a randomized block design with the treatment of five shallot cultivars and five replications. Molecular analysis of armyworm larvae was carried out using the Polymerase Chain Reaction (PCR) method using forward Lep_F1 and reverse Lep_R1 primers at the Cytochrome Oxidase Subunit I (COI) gene. Our results indicate that the period of adult pest infestation has been seen since the emergence of plants, namely 7 days after planting (dap). The colonization period begins at 21 (dap), when plants and larvae begin to grow. The development of the egg and larva population was seen when the plants totaled 21 (dap) (for eggs) and 28 dap (for larvae). The most preferred shallot cultivars are "Bali Karet" and "Bima Brebes". Armyworm larvae, including S. exigua, were identified as related to the same group as isolate larvae from China, India, Pakistan, Thailand, and Japan. These findings indicated that S. exigua preferred the two cultivars of shallots in the fields and emerged at 21 dap. This shows that insect management activities must be carried out systematically both when the shallots plants are young, pre- and post-harvest. Control with natural enemies can also be done for further research.